IMPLEMENTATION OF THE ROAD MAP POLICY FOR BUREAUCRATIC REFORM AT THE INSTANTIONAL LEVEL (Study at the Regional Secretariat of Konawe Regency, Southeast Sulawesi Province) - Reski Melyana Melamba; Soesilo Zauhar; Ainul Hayat (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Bureaucratic reform has become a very important concept in government administration. In Indonesia, bureaucratic reform has been ongoing for two decades and is systematically regulated through Presidential Regulation Number 81 of 2010 concerning the Grand Design of Bureaucratic Reform for 2010-2024 with the aim of achieving a World Class Bureaucracy by 2025. However, in its implementation, the bureaucratic reform policy is ongoing to date. This has not yet shown an impact on improving governance and achieving development targets, especially in regional governments (Hermawan et al, 2020). According to the Ministry of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia, the number of regional governments that have implemented bureaucratic reform programs is 200 out of 500. This is because bureaucratic reform regulations are too complicated, even though there has been a system approach that has been developed, the implementation of bureaucratic reform policies has not yet been implemented. running as expected (Dwiyanto, 2015). This research focuses on the implementation of the bureaucratic reform road map policy at the Regional Secretariat of Konawe Regency, Southeast Sulawesi Province. The results of the research show that the implementation of the bureaucratic reform road map policy at the Regional Secretariat of Konawe Regency, Southeast Sulawesi Province has not been effective and has not been completed in several areas of change analyzed, although several areas of change have shown relatively good progress, there are still several aspects that need to be implemented. has not been effective and reached the optimal level as expected.Keywords:Bureaucratic Reform, Policy Implementation, Road Map, Regional Government